Peran Teknologi Manajemen Informasi dalam Memperlancar Pengarsipan Surat Kantor di SMA Tunas Pelita Binjai - Putri, Dinda; Asyari, Gita; Samahangga Manik, Khalid (LPPM Universitas 17 Agustus 1945 Semarang, 2024)
This study aims to explore the role of Information Management Technology (TMI) in expediting the filing of office letters at SMA Tunas Pelita Binjai. The main focus of this research is to analyse the impact of TMI implementation on efficiency, information disclosure, and service quality improvement in letter filing. The research methods used include centralised interviews with teachers and TU staff as respondents, analysis of system usage data, and business process modelling. The results show that the implementation of TMI has contributed significantly in improving the efficiency of office letter filing at SMA Tunas Pelita Binjai. The integrated database system allows the storage and management of letters to be more structured and easily accessible. In addition, TMI also enables higher information disclosure and improved quality of school administration services. The integration of TMI not only provides internal benefits to the office in records management, but also contributes to the improvement of the office's image and reputation in service to stakeholders. By continuing to maintain and develop the existing TMI system, it is expected that SMA Tunas Pelita Binjai can continue to improve its performance and services to achieve better standards in the future.